2011
DOI: 10.1021/pr101075e
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Phosphotyrosine Signaling in Glioblastoma Identifies STAT5 as a Novel Downstream Target of ΔEGFR

Abstract: An in-frame deletion mutation in Epidermal Growth Receptor (EGFR), ΔEGFR is a common and potent oncogene in glioblastoma (GBM), promoting growth and survival of cancer cells. This mutated receptor is ligand independent and constitutively active. Its activity is low in intensity and thought to be qualitatively different from acutely ligand stimulated wild type receptor implying that the preferred downstream targets of ΔEGFR play a significant role in malignancy. To understand the ΔEGFR signal we compared it to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 26 publications
2
42
0
Order By: Relevance
“…As we have shown previously, this modest decrease in uPAR is accompanied by a major increase in uPA expression, which has the net effect of activating uPAR signaling (42,53). This shift in GBM cell signaling has been implicated in promoting survival of tumor cells treated with EGFR-targeting drugs and in promoting GBM cell migration (42,50,52).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…As we have shown previously, this modest decrease in uPAR is accompanied by a major increase in uPA expression, which has the net effect of activating uPAR signaling (42,53). This shift in GBM cell signaling has been implicated in promoting survival of tumor cells treated with EGFR-targeting drugs and in promoting GBM cell migration (42,50,52).…”
Section: Discussionmentioning
confidence: 65%
“…Nevertheless, tumors in which EGFRvIII is identified tend to be highly aggressive (43,51). This may reflect novel co-receptor interactions in the cells that express EGFRvIII or activation of downstream signaling pathways that are unique to EGFRvIII (52). We previously showed that in EGFRvIII-expressing GBM cells, membrane-anchored uPAR functions as an important co-receptor promoting activation of STAT5b (42).…”
Section: Discussionmentioning
confidence: 99%
“…Although EGFRvIII signaling has been extensively studied in GBM cell lines, the molecular mechanisms of increased tumorigenesis driven by EGFRvIII overexpression in human tumors have not been fully elucidated (20,21). In addition, tissue culture conditions dramatically change the genetic and molecular characteristics found in primary human tumors.…”
Section: Glioblastoma Multiforme (Gbm)mentioning
confidence: 99%
“…48 Chumbalkar et al performed a tyrosine-directed search for signaling events downstream of DEGFR (EGFRviii) and identified STAT5 phosphorylation at Y699 as a key event. 56 Later, Latha et al demonstrated that EGFRviii cooperated with STAT5 to regulate the Bcl -xL promoter. 57 This prompted us to investigate the role of JAK/STAT inhibitor cucurbitacin-I and the Bcl -2/Bcl -xL antagonist ABT-737 in glioma cell lines.…”
Section: Introductionmentioning
confidence: 99%